Assessment of malignant melanoma lesions using violet‐light dermoscopy: A case report. Issue 7 (17th April 2022) - Shu, Juri; Yamamoto, Yosuke; Aoyama, Kazuhiro; Togawa, Yaei; Kishimoto, Takashi; Matsue, Hiroyuki
Abstract: Malignant melanomas often present with irregular shapes and in multiple shades of brown under white light. Dermoscopy is used to diagnose malignant melanomas; nevertheless, it is often difficult to differentiate malignant melanoma from healthy pigmented skin. The DZ‐D100 dermoscope (Casio Computer) is a digital camera equipped with a white light‐emitting diode (LED) and a violet LED, which can capture non‐polarized/polarized conventional dermoscopy images (CDS) as well as violet‐light dermoscopy (VLD) images. Since the absorption wavelength of melanin approaches that of ultraviolet rays, VLD with a wavelength of 405 nm can be used to visualize it. This camera allows three images with the same composition to be captured simultaneously. In this case, we performed dermoscopy with DZ‐D100 to determine the surgical resection margins of a melanoma of the heel in a 76‐year‐old woman. The pale‐colored lesions that were difficult to demarcate by CDS were clearly visible by VLD, presenting as dark areas in the grayscale images. Preoperatively determined lesion boundaries with CDS in combination with VLD were histologically more accurate than those with conventional CDS alone. Therefore, the combination of CDS and VLD may reveal the distribution of subtle pigmentation of fine melanin in the skin, making it easier to distinguish between lesions and healthy skin. As one of the limitations, parts of the heel with thick stratum corneum were also observed to be dark gray in the VLD images. Therefore, the evaluation of pigment lesion should be performed by comparing both CDS and VLD.